Generative Design of A 6-Axis Quadcopter Drone for Weight Optimization - Md Ghazaly, Mariam; Tze Jun, Kueh (International Journal of Integrated Engineering, 2023)
A drone is an Unmanned Aerial Vehicle (UAV) that can be remotely controlled through software-controlled flight plans using embedded systems. The major challenge in UAV is to obtain the unique structure design of the 6-Axis quadcopter drone through different applied parameters. Hence, this research aims to design the best structure of a UAV drone, which optimizes the shape of materials and manufacturing methods while saving the cost of materials, parts, and design time during the manufacturing and assembly process. In this research, a mechanical structure of a UAV drone is sketched in Autodesk Inventor and Autodesk Fusion 360. Generative design is a process of defining the constraints and forces of the imaginary design; then, the software will calculate all the shape possibilities that satisfy the initial design parameters. Exploration tools such as detailed thumbnails, filters, and customizable scatter plots will assist in achieving the best match UAV drone design and its manufacturing requirements. The UAV using the generative design was set to a total weight less than 1kg, whereby the optimized maximum stress analysis is achieved at 5.028MPa with 83.00%, maximum displacement analysis at 0.666mm with 45.44%, and production time is at 15.5hours with 61.25% which improve the UAV weight optimization.